Peritonitis from injury of an aberrant subvesical bile duct during laparoscopic cholecystectomy: A rare case report. Issue 9 (9th July 2018) - Song, Sanghyun; Jo, Sungho
Key Clinical Message: Aberrant subvesical bile ducts are rare anatomical structures. Damage to these ducts leads to bile leakage and can result in life‐threatening complications. Surgeons should be cautious that such a structure may be present, and surgery should be performed with the correct surgical field to prevent damage to these structures. Abstract : Aberrant subvesical bile ducts are rare anatomical structures. Damage to these ducts leads to bile leakage and can result in life‐threatening complications. Surgeons should be cautious that such a structure may be present, and surgery should be performed with the correct surgical field to prevent damage to these structures.